Homogenization of elliptic problems involving interfaces and singular data. (December 2019) - Amar, Micol; De Bonis, Ida; Riey, Giuseppe
Abstract: We prove existence and homogenization results for a family of elliptic problems involving interfaces and a singular lower order term. These problems model heat or electrical conduction in composite media.